PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI EKSTRINSIK TERHADAP KEPUASAN KERJA KARYAWAN PT. ANDI DWI HARYANTO TUNAS MERAPI WONOGIRI - Pradita Ujiyanto; Jajuk Herawati; Prayekti Prayekti (Universitas Sarjanawiyata Tamansiswa, 2020)
This research aims to determine how the influence of, transformational leadership style on job satisfaction, extrinsic motivation on job satisfaction,both of transformational leadership style and extrinsic motivation to job satisfaction.This type of research is quantitative research, research variables are transformational leadership style (X1), extrinsic motivation (X2) and job satisfaction (Y). The population in this research were all permanent employees from PT. Andi Dwi Haryanto Tunas Merapi Wonogiri totaling 41 people and also used as theresearch sample. Data sources used in this research are primary data. Data collection methods in this researchwere using form of questionnaires. Using multiple regression analysis techniques. Which is supported by hypothesis testing, F test and by passing the classic assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test.Based on the results of the research there is a significant positive effect between transformational leadership style and extrinsic motivation on job satisfaction. In this research, transformational leadership style (X1) has a positive and significant influence on job satisfaction (Y). And extrinsic motivation (X2) has a positive and significant influence on job satisfaction.Keywords: transformational leadership style , extrinsic motivation , job satisfaction